"I was Right about Vaccination": Confirmation Bias and Health Literacy in Online Health Information Seeking. Issue 2 (1st February 2019) - Meppelink, Corine S.; Smit, Edith G.; Fransen, Marieke L.; Diviani, Nicola
Abstract : When looking for health information, many people turn to the Internet. Searching for online health information (OHI), however, also involves the risk of confirmation bias by means of selective exposure to information that confirms one's existing beliefs and a biased evaluation of this information. This study tests whether biased selection and biased evaluation of OHI occur in the context of early-childhood vaccination and whether people's health literacy (HL) level either prevents or facilitates these processes. Vaccination beliefs were measured for 480 parents of young children (aged 0–4 years) using an online survey, after which they were exposed to a list of ten vaccine-related message headers. People were asked to select those headers that interested them most. They also had to evaluate two texts which discussed vaccination positively and negatively for credibility, usefulness, and convincingness. The results showed that people select more belief-consistent information compared to belief-inconsistent information and perceived belief-confirming information as being more credible, useful, and convincing. Biased selection and biased perceptions of message convincingness were more prevalent among people with higher HL, and health communication professionals should be aware of this finding in their practice.